Population ecology and classical biological control of forest insect pests in a changing world - Fischbein, Deborah; Corley, Juan Carlos (Elsevier, 2022)
Forests are important for climate regulation and provide wood and fiber to an increasing human population. Forest systems encompass a large part of the world’s land surface area and they are increasingly threatened by several abiotic and biotic factors, including invasive alien species. Generally, the management of damaging nonnative forest insects relies strongly on classical biological control. This is because other Integrated Pest Management tactics may not be readily applicable in forests as these are typically long-lived and structurally complex systems. Given the marked increase in the arrival and establishment of alien forest insects, and the worldwide development of commercial forestry, there is a growing need for classical biological control to achieve persistent pest suppression and to bar the geographical spread of alien pests. Despite much progress in the identification, rearing capacity and release protocols of natural enemies, a limited understanding of pest population ecology and the underlying driving factors, can hinder the effectiveness of classical biological control programs. In this review, we explore the importance of population ecology of forest insects and highlight ecological hypotheses that can serve to lay the groundwork for improved pest management programs in the context of climatic change. While we emphasize the value of classical biological control to manage insect pests in forest systems, especially alien species in novel environments such as in commercial plantations, we draw attention to the need for a better understanding of the processes determining forest insect population dynamics, to secure successful and sustainable pest management programs.